2013
DOI: 10.1053/j.ajkd.2013.01.027
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Controlled Study of Kidney Donors: Baseline and 6-Month Follow-up

Abstract: Background Most previous studies of living kidney donors have been retrospective and have lacked suitable healthy controls. Needed are prospective controlled studies to better understand the effects of a mild reduction in kidney function from kidney donation in otherwise normal individuals. Study Design Prospective, controlled, observational cohort study. Setting & Participants Consecutive patients approved for donation at 8 transplant centers in the US were asked to participate. For every donor enrolled, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
59
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 65 publications
(38 reference statements)
13
59
0
1
Order By: Relevance
“…LKDT is considered a safe procedure for donors, and there seems to be no increased risk of deteriorated renal function or other relevant disabilities like hypertension or proteinuria [7][8][9]. Nevertheless, mild changes after kidney donation similar to chronic kidney disease have been reported [10][11][12]. There appears to be some risk of the development of end-stage renal disease (ESRD) in the long term [13].…”
Section: Introductionmentioning
confidence: 99%
“…LKDT is considered a safe procedure for donors, and there seems to be no increased risk of deteriorated renal function or other relevant disabilities like hypertension or proteinuria [7][8][9]. Nevertheless, mild changes after kidney donation similar to chronic kidney disease have been reported [10][11][12]. There appears to be some risk of the development of end-stage renal disease (ESRD) in the long term [13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, controls were assembled from the general population, and obviously did not undergo the same rigorous testing that donors face before surgery. A group from the U.S. and Canada recently published 6-month data on 201 donors and matched controls followed since nephrectomy [32]. Though there were no differences in blood pressure, a longer follow-up time may be needed.…”
Section: Blood Pressurementioning
confidence: 99%
“…11 Several important new reports, all using controls with health status comparable to donors at the onset of observation, have now further expanded our understanding of donor risk. In a prospective evaluation of living donors (n=201) and matched healthy concurrent controls (n=198) at eight centers, Kasiske et al 12 reported mean GFR 6 months postdonation as 68610 ml/min per 1.73 m 2 that was accompanied by significant alteration in the calcium/phosphorus/parathyroid axis. Donor Nephrectomy Outcomes Research (DONOR) Network investigators, in a cross-sectional study of 198 previous donors, documented similar changes plus increased fibroblast growth factor 23 levels.…”
mentioning
confidence: 99%
“…The works by Kasiske et al 12 and the DONOR Network investigators 13 document preservation of renal function without significant proteinuria in the overwhelming majority of previous donors. Additionally, regardless of hazard ratios or cohort characteristics, the incidence of ESRD and mortality among previous donors is very low over very lengthy periods of time.…”
mentioning
confidence: 99%
See 1 more Smart Citation